1977
DOI: 10.1111/j.1365-3083.1977.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE in Human Urine and Milk

Abstract: IgE was found in urine from healthy adult volunteers at very low levels (approximately 0.003-0.010 IU/ml), corresponding to a 24-h excrection rate of 3-16 IU. IgE was not detected in 36 out of 47 samples of milk and colostrum. In samples from six women the protein was present at low concentration 1-2 days postpartum but was not detected in later samples (usually day 5 or 6). Mammary secretions from four allergic donors were studied, and IgE was detected at low concentrations in samples from the two most severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
(4 reference statements)
0
5
1
Order By: Relevance
“…The results of our study of milk are much lower than those reported by others who used RIST [Bennich and Johansson 1971;Underdown et al, 1976: Gleich et al, 1977 but they agree with those obtained with DAB and PRIST [ Underdown et al, 1976;Turner et al, 1977;Bahna et al, 1982]. The correlation with IgA, which is known to be locally produced, the lack of correlation with serum IgE, the rather high milk/ serum IgE ratio (mean: 0.024; range: 0.005-0.045) in comparison to similar ratios reported for albumin (0.01) [Underdown et al, 1976] and IgG (0.008) [Brandtzaeget al, 1970] suggest a minor local produc tion of IgE in the mammary gland.…”
Section: Discussioncontrasting
confidence: 56%
“…The results of our study of milk are much lower than those reported by others who used RIST [Bennich and Johansson 1971;Underdown et al, 1976: Gleich et al, 1977 but they agree with those obtained with DAB and PRIST [ Underdown et al, 1976;Turner et al, 1977;Bahna et al, 1982]. The correlation with IgA, which is known to be locally produced, the lack of correlation with serum IgE, the rather high milk/ serum IgE ratio (mean: 0.024; range: 0.005-0.045) in comparison to similar ratios reported for albumin (0.01) [Underdown et al, 1976] and IgG (0.008) [Brandtzaeget al, 1970] suggest a minor local produc tion of IgE in the mammary gland.…”
Section: Discussioncontrasting
confidence: 56%
“…studies have found either small or unmeasurable quantities (16,17). Our own studies confirm these observations, as IgE was detected in concentrations of 0.5-6 IU/ml in only 41% of the colostrum samples analyzed (16/39) and was undetectable (under 0.5 IU/ml) in the remainder.…”
Section: Fig 2 Igd In Colostrum and Plasma (Distribution And Mean Andmentioning
confidence: 99%
“…Studies of IgE in milk have been few. Two investigators found either absent or low concentrations of IgE in milk compared with those in serum and concluded that local production or selective secretion by the mammary gland does not take place (16,17).…”
Section: Speculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is no significant IgE synthesis in the urinary tract [48]. It is known that IgE-synthesizing plasma ceils are present not only in lymphoid tissue but also IgE Gammopathy in the lamina propria o f mucous membranes [49], Taking into consideration the structure of the IgE molecule, passive transport of IgE through any membrane would be difficult.…”
Section: Discussionmentioning
confidence: 99%